Understanding South-South Cooperation: A Comparative Analysis with North-South Cooperation Approaches - Zavarce Velasquez, Carlos David (Global South Review, 2024)
South-South Cooperation was first conceived at the 1955 Bandung Conference, which led to the foundation of the Non-Aligned Movement in 1961 and other important initiatives within the UN system, such as creating the G77 and elaborating the Buenos Aires Plan of Action. Since the beginning of the century, this cooperation modality has re-emerged and is now considered a catalyst for sustainable development. Given this context, this paper aims to analyze its ideological and political origins, definitions, and evolution, highlighting its importance as an instrument of foreign policy and development cooperation. In addition, a comparison between South-South and North-South Cooperation is made through five dimensions: ideas, institutions/political systems, interests, organizations, and vectors/schemes. Through this comparative approach, the author seeks to present consensual aspects of what is understood as South-South Cooperation and portray the diversity of strategies implemented by countries in the Global South.Keywords: South-South Cooperation; North-South Cooperation; Global South; sustainable developmen; BRICS